Mathematical modelling of HIV/AIDS transmission under treatment structured by age of infection - Ejigu, Amsalework Ayele (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc (Mathematical Sciences))--University of Stellenbosch, 2011.